Pengaruh Beban Kerja dan Totalitas Kerja terhadap Subjective Well-Being (SWB) Prajurit Pasmar 1 dalam Mendukung Tugas Pokok Korps Marinir - Febrianto, Erwin Tri; Triutomo, Gunawan; Simangunsong, Sikop Pauli (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The Indonesian National Army (TNI) is part of the general public that is specially prepared to carry out the task of defending the country and nation, as well as maintaining national defense and security. The Indonesian Navy has the task of carrying out the duties of the TNI naval force in the field of defense, enforcing the law and maintaining security in the national jurisdictional sea area in accordance with the provisions of national law and ratified international law, carrying out the duties of the TNI in the development and development of naval force in supporting the main tasks of the Marine Corps, namely fostering strength and capability and operational readiness as a landing force of the Indonesian Navy in the context of projecting power to land by sea. This research is a type of descriptive quantitative research with a survey method. The purpose of this study was to determine whether there is an effect of workload on the Subjective Well-Being (SWB) of Pasmar I soldiers in supporting the main tasks of the Marine Corps, whether there is an effect of total work on the Subjective Well-Being (SWB) of Pasmar I soldiers in supporting the main tasks of the Marine Corps and whether there is an effect of workload and total work simultaneously on the Subjective Well-Being (SWB) of Pasmar I soldiers in supporting the main tasks of the Marine Corps. obtained t-count value on the Workload variable of 5.933 and the t-table obtained is 1.649, the t-count value on the Work Totality variable obtained is 13.289 while the t-table obtained is 1.649, the f-count value on the Workload and Work Totality variables obtained is 938.881, meaning that if f count> f table and significance value <0.05. So it can be interpreted that there is an influence of Workload and Work Totality simultaneously on Subjective Well-Being.